The Effect of Taxpayer Awareness and Awareness on Taxpayer Compliance Paying Land and Building Taxes in Rancakalong District, Sumedang Regency - Ervina Puji Lestari; Gunawan Wibisana; Sophia Annisa (LPPM Universitas Sebelas April, 2020)
The core of the problem in this research is about compliance with paying Land and Building Tax (PBB) in Rancakalong sub-district, Sumedang Regency. This study aims to determine the income of taxpayers, taxpayer awareness, taxpayer compliance, the magnitude of the effect of taxpayer income on tax compliance, the magnitude of the effect of taxpayer awareness on tax compliance, and the magnitude of the effect of income and taxpayer awareness together on tax compliance. compliance with paying PBB in Rancakalong District, Sumedang Regency. This research method uses quantitative methods with a survey approach. The sampling technique used simple random sampling method. The population of this research is individual taxpayers who are registered in Rancakalong District. The sample used in this study were 100 respondents. The data in this study were obtained primary (questionnaire). The analysis technique used is multiple regression analysis, correlation coefficient test, coefficient of determination, and hypothesis testing. Data processing using SPSS for windows 25 program. The results of this study indicate that income and awareness of taxpayers have a significant effect on compliance with paying PBB in Rancakalong District, Sumedang Regency.